The Role of Secretion Systems, Effectors, and Secondary Metabolites of Beneficial Rhizobacteria in Interactions With Plants and Microbes - Lucke, Miriam; Correa, Mario Gabriel; Levy, Asaf (Frontiers in Plant Science, 2020)
Beneficial rhizobacteria dwell in plant roots and promote plant growth, development, and resistance to various stress types. In recent years there have been large-scale efforts to culture root-associated bacteria and sequence their genomes to uncover novel beneficial microbes. However, only a few strains of rhizobacteria from the large pool of soil microbes have been studied at the molecular level. This review focuses on the molecular basis underlying the phenotypes of three beneficial microbe groups; 1) Plant-growth promoting rhizobacteria, 2) root nodulating bacteria, and 3) biocontrol agents. We focus on secreted bacterial proteins and secondary metabolites that mediate beneficial phenotypes within and around plant roots, and the mechanisms used to secrete these. We highlight the necessity for a better understanding of bacterial genes responsible for beneficial plant traits, which can be used for targeted gene-centered and molecule-centered discovery and deployment of novel beneficial rhizobacteria.